Retail Business Model in Assisting MSME Business Continuity in Medan City after the Covid-19 pandemic. - Rina Walmiaty Mardi,; Asmalidar,; Susilawaty, (RES MILITARIS, 2022)
Before the Covid-19 pandemic hit countries in the world including Indonesia starting in early 2020, Medan City, as the third largest city in Indonesia, as well as the largest city outside Java, had a fairly rapid development of the retail business. In 2020 and 2021 researchers have conducted research on MSMEs in the city of Medan. The formulation of the problem in this research is how to determine the model of cooperation for the modern retail market business with MSMEs in the city of Medan after the Covid-19 pandemic. . The purpose of this research is to find a partnership model between modern retail market businesses and MSMEs in Medan City after the Covid-19 pandemic. The research was conducted by conducting in-depth interviews, SWOT analysis, and Forum Group Discussions. The research was conducted using qualitative methods. In-depth interviews were conducted with respondents. Interview results were analyzed using SWOT analysis (Strength Weakness Opportunity Threats). Furthermore, the results of the SWOT analysis were discussed in 2 stages of FGD. From the results of the FGD which was attended by stakeholders, it was obtained results on how modern market retail businesses can play a role in the sustainability of MSMEs in Medan City after the Covid-19 pandemic. Ease of requirements, payment systems, compliance with standards, and the application of strict regulations are recommendations for the modern retail market, MSMEs and the Medan City government in forming a mutually supportive partnership model between Medan City MSME businesses and the modern retail market.